2022
DOI: 10.1111/jbi.14461
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of arboreal alligator lizards shed light on the geographical diversification of cloud forest‐adapted biotas

Abstract: Aim The proximate ecological and evolutionary processes underlying the high biodiversity of neotropical montane cloud forests are still very poorly understood. Climatic oscillations may have contributed to vicariance and cladogenesis, but also promoted secondary contact and erosion of genetic divergence. Here we tested whether geographical diversification – or its lack thereof – in a complex of arboreal alligator lizards is explained by range shifts during Quaternary climatic oscillations. Location Pine–oak an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
2
2
0
Order By: Relevance
“…Our study revealed an important role of landscape heterogeneity and restricted dispersal through unsuitable habitats in determining the marked genetic fragmentation of montane oak forests in the Andean Cordilleras, rejecting the hypothesis of persistent connectivity proposed in previous studies (Zorrilla‐Azcué et al, 2021). Our genomic data support that elevational displacements and corresponding pulses of population merging and fragmentation at local to regional scales were not sufficient to erode the genetic structure of present‐day oak populations and, on the contrary, probably contributed to fuel their geographical diversification (e.g., Gutiérrez‐Rodríguez et al, 2022; Nevado et al, 2018). Future genomic‐based demographic reconstructions for a representative number of taxa of the different vegetation belts in a comparative framework might help to gain further insights into the dynamics of Andean biotas in response to Quaternary climatic oscillations (e.g., see Helmstetter et al, 2020 for a forest community in tropical Africa).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our study revealed an important role of landscape heterogeneity and restricted dispersal through unsuitable habitats in determining the marked genetic fragmentation of montane oak forests in the Andean Cordilleras, rejecting the hypothesis of persistent connectivity proposed in previous studies (Zorrilla‐Azcué et al, 2021). Our genomic data support that elevational displacements and corresponding pulses of population merging and fragmentation at local to regional scales were not sufficient to erode the genetic structure of present‐day oak populations and, on the contrary, probably contributed to fuel their geographical diversification (e.g., Gutiérrez‐Rodríguez et al, 2022; Nevado et al, 2018). Future genomic‐based demographic reconstructions for a representative number of taxa of the different vegetation belts in a comparative framework might help to gain further insights into the dynamics of Andean biotas in response to Quaternary climatic oscillations (e.g., see Helmstetter et al, 2020 for a forest community in tropical Africa).…”
Section: Discussionsupporting
confidence: 69%
“…Our genomic data support that elevational displacements and corresponding pulses of population merging and fragmentation at local to regional scales were not sufficient to erode the genetic structure of present-day oak populations and, on the contrary, probably contributed to fuel their geographical diversification (e.g., Gutiérrez-Rodríguez et al, 2022;Nevado et al, 2018) Flantua et al, 2019;Ornelas et al, 2019;Ramírez-Barahona & Eguiarte, 2013), which is still very limited compared to the welldocumented glacial-interglacial dynamics experienced by temperate biotas (Hewitt, 2004;Stewart et al, 2010). Ongoing biogeographical research in the tropical Andes guarantees future opportunities to further study the consequences of Quaternary climate change in this biodiversity hotspot (e.g., Flantua et al, 2019;Hazzi et al, 2018;Muñoz-Ortiz et al, 2015;Nevado et al, 2018;Sanín et al, 2022) and to gain further insights into the proximate ecological and evolutionary processes that have contributed to its extraordinary levels of endemism (Kier et al, 2009;Myers et al, 2000).…”
Section: Con Clus Ionssupporting
confidence: 60%
“…Hypothesized causes of this diversity remain poorly tested, but interrelated biological, geological, and climatic factors are likely at play [5,6]. Many authors generally agree that complex historical processes of mountain formation, together with paleoclimatic events, created biogeographic barriers correlated with speciation in many Middle American vertebrates [7][8][9][10][11][12][13]. Today, striking and emblematic species of birds [14,15], snakes [16,17], frogs [18,19] and salamanders [20,21] live in these mountain woodlands and nowhere else.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the generation of biodiversity in this region have been the subject of numerous investigations (Bryson et al, 2011 ; DeRaad, Applewhite, et al, 2023 ; Mastretta‐Yanes et al, 2015 ; Ornelas et al, 2010 ; Sullivan et al, 2000 ; Venkatraman et al, 2019 ; Zarza et al, 2016 ). While vicariance seems to have played a major role in speciation—whether via mountain uplift (Bryson Jr et al, 2012 ; Bryson Jr & Riddle, 2012 ; Castoe et al, 2009 ) or Pleistocene glacial cycles (Gutiérrez‐Rodríguez et al, 2022 )—dispersal into and out of Mesoamerica has also been a key factor structuring communities (López‐García & Morrone, 2022 ; Ornelas et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%